The Effects of Ecologic Condition on Antimicrobial Activity of Endemic Herbal Extracts in Fars Province - Abdorasoul Zakerin; Elaheh Ahmadi; Mehdi Fasihi-Ramandi; Sara Abdollahi; Alireza Molazadeh; Somayeh Jafari; Ghader Allahverdi; Seyed Amin Kouhpayeh; Mohammad Hasan Meshkibaf (Journal of Advanced Biomedical Sciences, 2015)
Background & Objectives: Ecologic conditions affect production of effective pharmaceutical products. We evaluate the effect of ecologic conditions on antibacterial effects of herbal plants in Fars.